Perancangan Alat Bantu Home Scaffolding - Dewansyah, Agly Prasta; Yusianto, Rindra; Jazuli, Jazuli (Universitas Dian Nuswantoro, 2017)
Scaffolding is a tool commonly used in installation processes that are similar in shape to stairs. Based on survey results to existing scaffolding users, it is concluded that it needs to be redesign because it is too heavy and inflexible. This is why many scaffolding users are not satisfied. In this research, will be designed a scaffolding that suits the needs of consumers by using rational methods and anthropometric approach. The use of rational methods aims to obtain the objectives, functions, details, and selection of scaffolding materials, while the anthropometric approach is used to determine the size of the scaffolding according to Indonesian posture. From the research that has been done, the results obtained that the scaffolding to be designed has to can be set height, can be folded so that it can save space, lightweight, easy to carry and safe to use. Testing of designed scaffolding gives results that the new design is able to withstand loads of up to 2500 Newtons (254.94 Kg) making it safe to use for 2-3 people.